Urban Toponyms as Linguistic Markers of “Owning” the Space - Vasiljeva, Natalia (Acta humanitarica academiae Saulensis, 2025)
The article examines unofficial urban toponyms as markers of mental development of space and as markers of regional identity. A multidisciplinary approach to unofficial urban toponyms is suggested that combines the methods of linguistics with the methods of cultural geography on the basis of the “own-alien” opposition as an integrating parameter. The concept of vernacular region used in cultural geography and expediency of its application for onomastic studies is discussed. Vernacular regions are loaded with not only territorial, but also social and emotional sense and relate to mental maps. The identity of mental map is a sine qua non of the “own” community, and the correct usе of a toponym is a language criterion for passing the “own-alien” test. Also, the article provides a comprehensive overview of the studies concerning the notion of unofficial urbanonyms and approaches to their classification and categorization. An important feature implying that an urban object is fixed on the mental map of a local community is its ability to be a reference point in everyday city life and communication. Such objects are given unofficial names, the use of which in conversation is similar to using a code word. The author introduces a parameter of toponym markedness, which is understood similar to how it is interpreted in stylistics, namely: the unit standing out against similar ones. Marked forms include, in particular, those that cause an alogism of the utterance, cf. the expression that has become a Moscow topographical meme: на Ноге у Головы ‘on the foot by the head’, which means the place in the lobby of the metro station Китай-город, which until 1990 was called Площадь Ногина, near the sculpture in the form of a head of revolutionary activist Viktor Nogin. In the final part of the article, another class of names associated with toponyms is considered from the point of view of the “own-alien” opposition. These are katoikonyms – names of residents of a certain locality. According to the principles of substantive word formation in Russian, it is possible to produce derivatives with various suffixes, cf. Смоленск – смоленцы, смоляне, смоляки. In practice, the current use of these forms in the regional press, blogs and forums demonstrates that the city residents not only select the only one “correct” form (in this case смоляне), but also actively reject “incorrect” forms of the katoikonym, especially from “strangers” to the local people (journalists, politicians). The main conclusions of the article include the following. Space exploration takes place not only physically, but also mentally and emotionally. Unofficial toponyms serve as language markers of “owning” the space. In the study of unofficial toponymy, a multidisciplinary approach that integrates the achievements of onomastics, cultural anthropology, and cultural geography that is based on the “own-alien” opposition seems to be efficient. The unofficial name of a place is interpreted through this opposition: the knowledge and use of such names offer a criterion for establishing regional identity. In conclusion, it is emphasized that unofficial toponyms have their own life cycles, so their lexicographic fixation is very important not only for toponomastics, but also for urban and regional studies.